Catheter Ablation of Atrial Fibrillation in Patients at Low Thrombo‐Embolic Risk: Efficacy and Safety of a Simplified Periprocedural Anticoagulation Strategy. (18th April 2013) - DUYTSCHAEVER, MATTIAS; BERTE, BENJAMIN; ACENA, MARTA; DE, GRIM; BUN, SOK‐SITHIKUN; VAN, FREDERIC; VANDEKERCKHOVE, YVES; TAVERNIER, RENE
Aspirin and Low Molecular Weight Heparin in Patients Undergoing Catheter Ablation of AF Background To prevent thrombo‐embolic (TE) events during ablation of atrial fibrillation (AF), warfarin is recommended in all patients irrespective of baseline TE risk. We evaluated the efficacy and safety of a simplified periprocedural anticoagulation strategy of aspirin (ASA) and low molecular weight heparin (LMWH) in patients at low TE risk. Methods We collected data from 214 low TE risk patients (CHADS2 score ≤1 and no warfarin at baseline) undergoing pulmonary vein isolation. After discontinuation of ASA, periprocedural antithrombotic therapy consisted of therapeutic subcutaneous LMWH injections (nadroparin 1 mL/kg once daily) from 10 days before until 10 days after the procedure, followed by ASA in all patients. At the time of procedure, transesophageal echocardiography (TEE) was not performed on a routine basis. During the procedure, unfractionated heparin was administered to achieve an ACT between 350 and 400 seconds. Data on TE events (stroke or transient ischemic attack), cardiac tamponade/perforation, and major vascular access complications within 3 months after the procedure were collected. Results Mean CHADS2 was 0.3 ± 0.5. TEE was performed in 3% of patients. No periprocedural TE events occurred. No cardiac tamponade/perforation was observed. Major vascular access complications occurred in 3 patients (1.4%). No permanent injury was observed (0%). Conclusion In selected low TE risk patients undergoing ablation for AF, a short period of periprocedural therapeutic anticoagulation with LMWH together with aspirin is an effective and safe strategy to prevent TE events. If confirmed in a randomized trial, this approach might simplify periprocedural antithrombotic management in ablation of selected AF patients.